The role of the media in reducing the phenomenon of violence inside stadiums - bouadjnak, Kamel (sports creativity, 2025)
This research aims to explore the role of the press in mitigating violence. Incidents of violence and rioting in sports stadiums are frequent and escalating, impacting the sports movement within society. We have diligently sought to study the causes and effects of these violent phenomena through scientific and analytical research, addressing the root causes that can protect stadiums and sports venues from the evils of violence. We highlight the role of the media in this endeavor. Football has garnered significant attention from the public and internationally renowned political figures, among other factors, contributing to its status as one of the most important and popular sports in the world. However, despite this popularity, its history is marred by acts of violence, which are contrary to morality and the overall purpose of the sport. In short, football stadiums are rarely free from violence, which heightens the psychological and emotional excitement of the audience and can lead to aggressive behavior, especially if the violence witnessed is perceived as justifiable. This is particularly true for young people and teenagers who imitate star players, such as the violence used by the Algerian-born player Zinedine Zidane against the Italian Materazzi in the 2006 World Cup final in Germany, and the clashes between Algerian and Egyptian fans during the World Cup qualifiers. The concept of football is inextricably linked to sports media, both print and broadcast, which serve as a bridge between football and the fans, players, coaches, and educators, giving rise to a specialized field within the sport. Our research aims to determine the extent to which sports media, in both its print and broadcast forms, contribute to reducing violence in stadiums. This choice of research stems from both subjective and objective considerations. The issue lies in the fact that the majority of fans pay close attention to print sports media, following and reading most newspapers and magazines regularly. Furthermore, print media often addresses the phenomenon of violence and attempts to mitigate it. The majority of fans confirmed this through questions posed to journalists on the subject. It became clear to us that most of the articles selected by newspapers address and correct the issue with the aim of raising awareness, promoting sportsmanship, and offering modern and effective scientific methods and solutions to reduce violence. Unfortunately, some magazines and newspapers treat it as a sensational topic to attract the public without any meaningful purpose. This will be discussed further in this article.